Can soil factors of Namibian fairy circles explain the absence of vegetation from them? - von Hase, Fabian (Department of Biological Sciences, 2020)
Fairy circles are an enigmatic feature of the pro-Namib zone of Namibia which is expressed in countless barren circles of 2 -12 m in diameter. In April 2010, 54 fairy circles were studied in the Namibrand Nature Reserve to investigate the hypothesis that their soils show differences to the soils of the surroundings which would lead to suppressed plant growth and the absence of vegetation from the circles. Characterisation, temperature profiling and a transplantation experiments were carried out in the field and soil collected in the field (from on-, off-circle and ant nests) was analysed for nutrients, field capacity, drying rate and used in a growth experiment (using wheat) in the glasshouse of the University of Cape Town. No distinct differences in soil nutrient levels, water) holding capacity or temperature were found for circle soils and the transplantation experiment did not yield any significant fit ness reductions of plants on circle when compared to the matrix. However, the growth experiment showed increased growth on ant nest and suppressed growth on circle soils and the drying rate of circle soils was significantly higher than that of matrix soils (F,3,33i = 9.91, p < 0.001 after 96 h of drying). I concluded that circle soils could dry out faster than roots manage to grow and that this may kill grass seedlings and keep circles bare. Secondly, the inhibited growth on soil from circles may be due to an inhibitory substance released by an organism other than ants due to increased growth on ant nest soil into these soils; however no culprit for this process was found and further study into this is warranted.